DEVELOPMENT OF CHITOSAN COATING PRODUCT CONTAINING BITTER GOURD EXTRACT TO DELAY ANTHRACNOSE DISEASE IN MANGO (Nativa, 2024)
Mangifera indica cv. ‘Nam Dok Mai’ is the most popular fruit in Asia and worldwide, but it often faces anthracnose disease both in the vegetative stage (on leaves) and the reproductive stage (on fruit). The symptoms of this disease affect low yield and limit export; therefore, the effect of coating to reduce the incidence of anthracnose disease in mango fruits is necessary. This research aimed to develop an edible chitosan coating containing bitter gourd extract. Mango fruits were coated with 0.5, 1.0 and 2.0% chitosan solution (70-75% deacetylation; 310-375 kDa) and appropriate 500 ppm bitter gourd extract. The result showed that chitosan coating with bitter gourd extract could not extend the shelf life of mango fruits and decrease the incidence of disease longer when compared with coatings with chitosan or bitter gourd extract alone. Further, it could also delay ripening. Disease incidence and lesion diameter on mangoes coated with 2% chitosan with bitter gourd extract was the most effective (P < 0.05) within 5, 7 and 10 days after storage. Weight loss in mangoes increases during ripening; however, chitosan coating can help reduce weight loss. Fruits coated with 1% chitosan were the best formula for reducing weight loss. Chitosan coating adding bitter gourd extract is the best choice to replace chemical treatment to obtain better quality before export or transportation. Desenvolvimento de produto de revestimento de quitosana contendo extrato de melão amargo para retardar a antracnose em manga RESUMO: Mangifera indica cv. ‘Nam Dok Mai’ é a fruta mais popular não só na Ásia, mas também em todo o mundo, mas frequentemente enfrenta uma doença de antracnose tanto no estágio vegetativo (nas folhas), quanto no estágio reprodutivo (na fruta). Os sintomas desta doença afeta o baixo rendimento e limita a exportação, portanto, o efeito do revestimento para reduzir a incidência da doença de antracnose em frutas de manga é necessário. Esta pesquisa teve como objetivo desenvolver um revestimento comestível de quitosana contendo extrato de melão amargo. As frutas de manga foram revestidas com 0,5, 1,0 e 2,0% de solução de quitosana (70-75% de desacetilação; 310-375 kDa) e 500 ppm apropriados de extrato de melão amargo. O resultado mostrou que o revestimento de quitosana com extrato de melão amargonão pode estender a vida útil das frutas de manga e diminuir a incidência da doença por mais tempo quando comparadas com os revestimentos apenas com quitosana ou extrato de melão amargo, e ainda, também pode atrasar o amadurecimento. A incidência de doenças e o diâmetro das lesões nas mangas revestidas com quitosana 2% com extrato de melão amargo foram os mais eficazes (P < 0,05) dentro de 5, 7 e 10 dias após o armazenamento. A perda de peso nas mangas aumenta durante o amadurecimento; no entanto, o revestimento de quitosana pode ajudar a reduzir a perda de peso. As frutas revestidas com quitosana 1% foram a melhor fórmula para redução da perda de peso. O revestimento de quitosana adicionando extrato de melão amargo é a melhor escolha para substituir o tratamento químico para obter melhor qualidade antes da exportação ou transporte.Palavras-chave: antracnose; melão amargo; quitosana; manga; doença pós-colheita.